Lipocalin-2 is a pathogenic determinant and biomarker of neuropsychiatric lupus. (January 2019) - Mike, Elise V.; Makinde, Hadijat M.; Gulinello, Maria; Vanarsa, Kamala; Herlitz, Leal; Gadhvi, Gaurav; Winter, Deborah R.; Mohan, Chandra; Hanly, John G.; Mok, C.C.; Cuda, Carla M.; Putterman, Chaim
Abstract: Neuropsychiatric manifestations in lupus (NPSLE) affect ∼20–40% of patients. In the central nervous system, lipocalin-2 (LCN2) can promote injury through mechanisms directly linked to NPSLE, including brain barrier disruption, neurotoxicity, and glial activation. Since LCN2 is elevated in lupus and has been implicated in neuroinflammation, we investigated whether LCN2 is required for the pathogenesis of NPSLE. Here, we investigated the effects of LCN2 deficiency on the development of neurobehavioral deficits in the B6.Sle1.Sle3 (Sle1, 3) mouse lupus model. Sle1, 3 mice exhibited depression-like behavior and impaired spatial and recognition memory, and these deficits were attenuated in Sle1, 3-LCN2KO mice. Whole-brain flow cytometry showed a significant increase in brain infiltrating leukocytes in Sle1, 3 mice that was not reduced by LCN2 deficiency. RNA sequencing on sorted microglia revealed that several genes differentially expressed between B6 and Sle1, 3 mice were regulated by LCN2, and that these genes are key mediators of the neuroinflammatory cascade. Importantly, LCN2 is upregulated in the cerebrospinal fluid of NPSLE patients across 2 different ethnicities. Our findings establish the Sle1, 3 strain as an NPSLE model, demonstrate that LCN2 is a major regulator of the detrimental neuroimmune response in NPSLE, and identify CSF LCN2 as a novel biomarker for NPSLE. Highlights: Lipocalin-2 (LCN2) has been implicated in neuroinflammation. Sle1, 3 lupus mice display depression and altered cognition. Neuropsychiatric deficits are attenuated in LCN2 knockout lupus mice. LCN2 in the CSF is a novel biomarker for neuropsychiatric lupus.